Structural heart disease review of TAVR in low-risk patients: importance of lifetime management - Moumneh, Mohamad B.; Damluji, Abdulla A.; Heslop, Andras W.; Sherwood, Matthew W. (Frontiers in Cardiovascular Medicine, 2024)
Aortic stenosis (AS) is the most prevalent forms of valvular heart disease (VA), affecting millions of patients on an annual basis. It carries significant risk for morbidity and mortality if left untreated. (1) Currently, no pharmaceutical therapy with proven effect in slowing the progression of AS exists. Thus, effective therapy relies upon timely diagnosis, surveillance in the early stages, and prompt treatment when indicated. (2) Transcatheter aortic valve replacement (TAVR) has changed the landscape for treatment of AS, resulting in greater awareness and diagnosis of the disease, and prompting calls for earlier therapy. In addition, while TAVR was initially approved in high-risk symptomatic patients with severe AS or those with prohibitive risk who were poor candidates for surgery, it is now the preferred therapy for all risk levels and for most patients with AS. (3) In this review, we aim to highlight the evidence supporting TAVR in low-risk patients, guidelines for clinical use, and continuing challenges for treatment of AS patients at both lower risk and younger ages.